Inclusion of Indigenous People in Technical and Vocational Training - Ghising, Dipak (Asian Journal of Population Sciences, 2025)
Indigenous people have poor socio-economic conditions and are excluded from the development mainstreaming, which has hindered equal participation. Therefore, the study analyses the participation of diverse caste ethnic groups in Technical Education and Vocational Training (TEVT), which is essential in improving the socio-economic condition and justice-based development of all people. For this purpose, a quantitative research design and secondary data were adopted using SPSS to examine the inclusion of Indigenous people in TEVT. The study population is training participants who completed a three-month level-one training certified by the Council for Technical Education and Vocational Training (CTEVT). This study included 570 participants, including gender, age, education, income, and caste ethnicity. As a descriptive result, 66 percent of Indigenous and 58 percent of female trainees participated in the TEVT program. Similarly, multinomial logistic regression analysis shows an association between indigenous people and TEVT, which is statistically significant (p<.0001); the Chi-Square value is 324.736; the model explains approximately 43.3 percent by Cox and Snell, 49 percent by Nagelkerke and 26.1 percent McFadden R-square. Caste ethnicity and TEVT have a positive relationship, which can contribute to improving socio-economic conditions. Therefore, policymakers, planners, and program designers can jointly use findings to effectively address the issues regarding the inclusion perspective in the TEVT program, which applies to justice-based development and ensures that no one is left behind.